Toward the Rhodium-catalyzed bis-hydroformylation of 1,3-butadiene to adipic aldehyde - Smith, Stuart; Rosendahl, Tobias; Hofmann, Peter (Organometallics, 2011)
The effects of the ligand to metal ratio, temperature, syngas pressure, partial pressures of H2 and CO, and new ligand structures have been examined on 12 of the most reasonable products resulting from the rhodium-catalyzed low-pressure hydroformylation of 1,3-butadiene. The selectivity for the desired linear dihydroformylation product, 1,6-hexanedial (adipic aldehyde), is essentially independent of all of these reaction parameters, except for ligand structure. However, the reaction parameters do have a substantial effect on the selectivity for the products, resulting from the branched addition of the rhodium hydride to the carbon-carbon double bond. The optimum reaction parameters and ligand have resulted in a so far unprecedented maximum selectivity of 50% for adipic aldehyde.
Gesehen am 18.10.2022